Copillar[5]arene Chemistry: Synthesis and Applications - Chen, Wenzhang; Vincent, Stéphane P. (Synthesis, 2022)
Research on pillar[n]arenes has witnessed a very quick expansion. This emerging class of functionalized macrocyclic oligoarenes not only offers host–guest properties due to the presence of the central cavity, but also presents a wide variety of covalent functionalization possibilities. This short review focuses on copillararenes, a subfamily of pillar[n]arenes. In copillararenes, at least one of the hydroquinone units bears different functional groups compared to the others. After having defined the particular features of copillararenes, this short review compares the different synthetic strategies allowing their construction. Some key applications and future perspectives are also described. 1 Introduction2 General Features of Pillar[5]arenes3 Synthesis of Functionalized Copillar[4+1]arenes4 Concluding Remarks
Keywords: copillararenes; supramolecular chemistry; macrocycles; host–guest compounds; phenols